Carbon Nanotube and Ethylene-Vinyl Acetate Based Soft Nanocomposite Film: Preparation and Characterization - Gopal, N.; Saxena, A.; Kumar, B.; Sahney, R. (Asian Journal of Chemistry, 2021)
Soft and conductive interfaces are valuable in wearable electronics as they are capable for integration of diverse classes of electronic and sensor technologies directly with living body which can be used as health monitoring systems. In present work, we explore the development of multi-walled carbon nanotube-ethylene vinyl acetate nanocomposite (MWCNT-EVA) film and their properties. Oxidation of MWCNT is known to improve their dispersion properties and increase the electrical conductivity of MWCNT-polymer nanocomposites. Thus, pristine MWCNTs (p-MWCNTs) and functionalized MWCNTs (f-MWCNTs) were further used as conductive filler to construct p-MWCNT-EVA and f-MWCNT-EVA nanocomposite films. The films were characterized by Fourier-transform infrared spectroscopy, scanning electron microscopy, energy dispersive X-ray analysis and electrochemical technique. The results indicated that the chemical oxidation of p-MWCNT generates carboxylic function at the p-MWCNT surface important for sensor fabrication. The concentration of carboxylic functional group in f-MWCNT higher than in nanocomposites. The f-MWCNT-EVA nanocomposite film electrode surface show much higher conductivitythan p-MWCNT-EVAnanocomposite film. Thus, the soft and flexible f-MWCNT-EVA nanocomposite films are effective for the development of electrochemical platform for biosensor fabrication in wearable applications.